Detection of Typhoid Fever by Immuno Chromatographic Test (ICT) and Antibiotic Susceptibility Pattern of Salmonella Typhi in Chittagong Metropoliton City - Islam, Nazneen Naher; Progga, Rawnak Chowdhury; Chowdhury, M Masudul Azad; Islam, Kamrun Nahar (Chittagong University Journal of Biological Sciences, 2024)
Typhoid fever caused by the Salmonella typhi is a disease of global distribution and one of the major health problems in many developing countries. In this study, clinically suspected thirty five patients were enrolled from different diagnostic centers of Chittagong city. We evaluated the reliability of Immuno Chromatographic Test (ICT) compared to different diagnostic methods like blood/serum culture and serological/Widal test for early detection of the disease. A total of 18 (51.43%) and 20 (57.14%) samples were found positive in culture method and Widal test, respectively, whereas 31 (88.57%) were found positive in ICT. Moreover, 13 culture negative and 11 Widal test negative samples were found positive in ICT. As the ICT showed satisfactory results compared to the other methods used in this survey, it can be considered as a reliable method for the early detection of typhoid infection. The study revealed several antibiotic resistant patterns by standard disc diffusion method, 12 (66.66%) out of 18 culture positives were found multi-drug resistant. The Chittagong Univ. J. B. Sci.,Vol. 10(1 &2):53-70, 2020